Composite herald patch – a novel morphological variant of pityriasis rosea detected by dermoscopy. - Chuh, A.; Zawar, V.; Fölster-Holst, R. (European Journal of Pediatric Dermatology, 2017)
We report a teenage girl with pityriasis rosea. Under dermoscopy, we found multiple tiny, annular, and scaly lesions outside and around the border of the herald patch on her anterior thoracic skin. We coined composite pityriasis rosea for this variant, and included such in the classification. We highlighted the might of dermoscopy in revealing tiny details of cutaneous lesions, and remarked on the advantages of utilising a set of diagnostic criteria in diagnosing this paraviral exanthem in clinical and research settings.